Malpractice of Notary Law Profession in the Form of Authentic Deed Forgery (Denpasar District Court Decision Study Number 89/Pid.B.2020/Pn Dps) - Agung Dwi Pramono; K Kuswardani (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Notaries are public offcial who carrying out their duties and authorities are based on the principles of honesty, trustworthiness, and impartiality. There is even a Notary in Denpasar Bali who commits a violation as stated in the Judge's Decision Number 89/Pid.B/2020/PN Dps.The purpose of the research to describes the Judge’s Decision from the act aspect and malpraktice form in criminal law perspective. The research is doctrinal, then secondary data is as main data (reference, legal document that are relevant to the problems). Data collecting through library research. Data analysis using criminal law principles. The result show that the act of notary in the Judge’s Decision accordance with Article 264 paragraph (1) and (2) jo Article 56 of the Penal Code. Therefor a notary makes a mistake and must be responsible. Furthemore, the act of notary is called criminal malpractice, but also standart of conduct.